PENGENALAN KONSEP BERHITUNG BAGI PEMULA (NON FORMAL) DENGAN MEDIA WARNA-WARNI - Yudha, Firma (Faculty of Cultural Studies, Universitas Brawijaya, 2022)
There was education a formal and also non formal a formal education and non formal definitely different intensity of the time that do even though the subjects given the same, an example in mathematics in the basic level. Recognition this activity aimed to provide knowledge to kids who do not school (formal), non so that they know the numbers to be able to count the base of. Method devotion is by lectures, discussion and practices. The one conducted by a team devotion in this activity is the stage, preparation and training in the implementation stage and the evaluation. From the introduction of the activities and operated the activities conducted there are 6, following are: 1) know the 1-10; 2) the rank; 3)counting the number of; 4) know the count and operation; 5) operates a sum that is using the picture; 6) operates colored using a photo of the reduction. This activity, succeded is conducted it turn out that kids love to play the media, colored although, takes time yet the sons feeling easily in the memorization and children able to operate the 1-10. Addition and subtraction in the process.